Beta Glucan Production from Two Strains of Agrobacterium sp in Medium Containing of Molases and Uracil Combine (Biodiversitas Journal of Biological Diversity, 2007)
Production of Î²-glucan by Agrobacterium sp is influenced by the composition of nutrition in the fermentation media. Molases has been used successfully by others in the fermentation media of S. cerevisiae to increase the yield of -glucan, and similarly, uracil has been used in the fermentation media of Agrobacterium sp to increase the yield of -glucan. Investigations to increase the yield of -glucan by two strains of Agrobacterium sp, i.e. A1.5 (reference) and B4.4 (local strain), have been carried out by addition of various combination of molases and uracil into fermentation media, i.e. 5%(v/v) molase-0,05%(b/v) uracil; 5% molase-0,025% uracil; 10% molase-0,05% uracil; and 10%molase-0,025% uracil. The Î²-1,3-glucan and Î²-1,2-glucan fractions were separated by extraction method. Beta-glucan concentration was determined as the glucose monomer using the phenol-sulphate spectrophotometric method at 490 nm. The protein content was determined by a modified Lowry-spectrophotometric method at 750 nm. The results showed that all combination of molases and uracil in the fermentation media of Agrobacterium sp A1.5 and B4.4 strains have increased both the dry-weight yield of Î²-glucan (crude) and the Î²- glucan content, with the highest was in a medium containing 10% molases-0,025% uracil combination. In the above medium, the A1.5 strain produced the highest Î²-glucan (7,5%) with the lowest protein content ( 8,4%) in the Î²-1,3-glucan fraction, while the Î²-glucan content in the Î²-1,2-glucan fraction were all lower than in the control media, while the protein content were all higher than in the control media. Inthe above media, the B4.4 strain produced the highest Î²-glucan, 7,2% in the Î²-1,3-glucan fraction, and 13,1% in Î²-1,2-glucan fraction, while the lowest protein content ( 8,4%) was in the Î²-1,3-glucan fraction. In conclusion, fermentation media of Agrobacterium sp A1.5 strain or B4.4 strain containing molase and uracil combination have increased both the dry-weight yield of total Î²-glucan (crude) and the Î²-glucancontent, while reduced the protein content. There is no clear FTIR spectrum difference between supposedly Î²-1,2-glucan fraction and Î²- 1,3-glucan fraction.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Beta glucan, Agrobacterium sp., Molases, Uracil